Services for Consumers Who Are Deafblind: Vocational Rehabilitation Agency Service Models Utilized and Their Effectiveness. (January 2019) - McDonnall, Michele C.; Cmar, Jennifer L.
Introduction: Little is known about how state-federal vocational rehabilitation agencies provide services to consumers who are deafblind. The purpose of this study was to investigate these service models and their effectiveness. Methods: A mixed-methods approach was utilized with data from interviews with 51 vocational rehabilitation agency administrators and the Rehabilitation Services Administration Case Service Report. Information about how these agencies serve deafblind consumers was combined with data from 2, 119 consumers served by those agencies to determine competitive employment rates based on service model type. Descriptive statistics, chi-square tests of independence, and logistic regression analysis were utilized. Results: Four vocational rehabilitation agency service models were identified: specialist, professional collaboration, specialist plus professional collaboration, and miscellaneous. Significant differences in competitive employment closure rates were found based on service model type, in both univariate and multivariate analyses. The specialist and professional collaboration models were superior to miscellaneous models. Discussion: This study is the first empirical evaluation of the effectiveness of vocational rehabilitation services for consumers who are deafblind. The results support two previous recommendations about providing services to consumers who are deafblind: establish a deafblind coordinator or specialist position and use a dual-case approach (collaboration between general-service agencies and those for people who are visually impaired). Implications for agencies: To improve competitive employment outcomes for individuals who are deafblind, vocational rehabilitation agency administrators should explore options for specialized deafblind positions and promote collaboration within and beyond their agency.